Effectiveness of Law Enforcement on Online Gambling Promotion Among Influencers - Seftiani; Hasuri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The sophistication of information technology makes online gambling increasingly developing. This also gives rise to the rampant promotion and advertising of online gambling, The important role of influencers is often associated with the increase in online gambling among the public. This study aims to evaluate the effectiveness of law enforcement against the promotion of online gambling by influencers in Indonesia, focusing on existing regulations, challenges in their implementation, and their impact on society. The research method used in this writing is that this research is designed with a normative juridical method. This research was carried out by researching library materials (secondary data) or library legal research. The results of the study show that despite the law enforcement efforts carried out, their effectiveness is still limited and requires a more comprehensive approach, including inter-agency cooperation and public education about the risks of online gambling. The recommendations include the need for clearer and more specific regulatory revisions and strengthening the capacity of law enforcement agencies to face challenges in this digital era. This research is expected to contribute to the development of more effective legal policies in tackling the promotion of online gambling by influencers in Indonesia.